DETERMINAN PERILAKU KERJA INOVATIF APARATUR SIPIL NEGARI PADA PEMERINTAH DAERAH DI PROVINSI SUMATERA UTARA - Sinaga, Anggun Tiur Ida; Sianipar, Herlina (UNIKA Santo Thomas, 2023)
The purpose of this study is to analyze the innovative work behavior of the local government employees in North Sumatera Utara.This study investigates the hypothesis of the antecedents of innovative work behavior consist of transformational leadership style, psychological empowerment, and affective commitment.The sampling technique used is stratified random sampling and purposive sampling,. This study includes 40 indicators and 786 participants.SmartPLS was used to process respondent data, which was then analyzed using the Structure Equation Model (SEM). In this study, three hypotheses are tested. This study uses a questionnaire as the main data collection tool from several selected areas. The results of this study are: (1) The transformational leadership style has a positive and significant effect on the innovative work behavior of local government ASN in North Sumatra Province; (2) psychological empowerment has a positive and significant effect on the innovative work behavior of local government ASN in North Sumatra Province; (3) affective commitment has a positive and significant effect on the innovative work behavior of local government ASN in the province of North Sumatra